Graphitic carbon and renewable hydrogen production from food waste. (Research'eu results magazine)
Graphitic carbon and renewable hydrogen will be two cornerstone resources of the green economy. Thanks to EU funding under the PLASCARB project and an innovative, low energy microwave plasma process, researchers aim to produce both from food waste.